Aptamer BC 007 - Efficient binder of spreading-crucial SARS-CoV-2 proteins. Issue 11 (November 2020) - Weisshoff, Hardy; Krylova, Oxana; Nikolenko, Heike; Düngen, Hans-Dirk; Dallmann, Andre; Becker, Susanne; Göttel, Peter; Müller, Johannes; Haberland, Annekathrin
Abstract: Corona virus disease 2019 (COVID-19) is a respiratory disease caused by a new coronavirus (SARS-CoV-2) which causes significant morbidity and mortality. The emergence of this novel and highly pathogenic SARS-CoV-2 and its rapid international spread poses a serious global public health emergency. To date 32, 174, 627 cases, of which 962, 613 (2.99%) have died, have been reported (https://www.who.int/westernpacific/health-topics/coronavirus, accessed 23 Sep 2020). The outbreak was declared a Public Health Emergency of International Concern on 30 January 2020. There are still not many SARS-CoV-2-specific and effective treatments or vaccines available. A second round of infection is obviously unavoidable. Aptamers had already been at the centre of interest in the fight against viruses before now. The selection and development of a new aptamer is, however, a time-consuming process. We therefore checked whether a clinically developed aptamer, BC 007, which is currently in phase 2 of clinical testing for a different indication, would also be able to efficiently bind DNA-susceptible peptide structures from SARS-CoV-2-spreading crucial proteins, such as the receptor binding domain (RBD) of the spike protein and the RNA dependent RNA polymerase of SARS-CoV-2 (re-purposing). Indeed, several such sequence-sections have been identified. In particular for two of these sequences, BC 007 showed specific binding in a therapy-relevant concentration range, as shown in Nuclear magnetic resonance (NMR)- and Circular dicroism (CD)-spectroscopy and isothermal titration calorimetry (ITC). The excellent clinical toxicity and tolerability profile of this substance opens up an opportunity for rapid clinical testing of its COVID-19 effectiveness. Abstract : Antiviral; Aptamer; BC 007; COVID-19; Re-purposing; SARS-CoV-2; Pharmaceutical science; Health sciences; Infectious disease; Pharmacology; Clinical research.